Langevin dynamcis simulations of driven polymer translocation into a cross‐linked gel. Issue 5 (March 2017) - Sean, David; Slater, Gary W.
Abstract : We investigate the dynamics of driving a polyelectrolyte such as DNA through a nanopore and into a cross‐linked gel. Placing the gel on the trans ‐side of the nanopore can increase the translocation time while not negatively affecting the capture rates. Thus, this setup combines the mechanics of gel electrophoresis with nanopore translocation. However, contrary to typical gel electrophoresis scenarios, the effect of the field is localized in the immediate vicinity of the nanopore and becomes negligible inside the gel matrix. Thus, we investigate the process by which a semiflexible polymer can be pushed into a gel matrix via a localized field and we describe how the dynamics of gel penetration depends upon the field intensity, polymer stiffness, and gel pore size. Our simulation results show that a semiflexible polymer enters the gel region with two distinct mechanisms depending upon the ratio between the bending length scale and the gel pore size. In both regimes, the gel fibers cause a net increase in the mean translocation time. Interestingly, the translocation rate is found to be constant (a potentially useful feature for many applications) during the predominant part of the translocation process when the polymer is stiff over a length scale comparable to the gel pore size.